Healthy lifestyle in children and adolescents and its association with subjective health complaints : findings from 37 countries and regions from the HBSC study - Marques, Adilson (2019)
© 2019 by the authors. Licensee MDPI, Basel, Switzerland. This article is an open access article distributed under the terms and conditions of the Creative Commons Attribution (CC BY) license (http://creativecommons.org/licenses/by/4.0/).